Peningkatan Keterampilan Teknologi Informasi untuk Optimalisasi Tata Kelola dan Proses Pembelajaran Taman Kanak-Kanak Aisyiyah Bustanul Athfal - Maziyyah, Nurul; Rahajeng, Bangunawati (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
Aisyiyah Busthanul Athfal Kindergarten (TK ABA) is a pre-primary educational institution established by the Muhammadiyah foundation, which is expected to create quality future generations in terms of formal, religious, and social education. In managing a kindergarten institution, a management system and adequate human resources are needed in terms of skills such as information technology (IT) skills. The purpose of the community service activities carried out is to introduce IT skills to the teachers of TK ABA Ponggalan, Giwangan. These community service activities were carried out by providing 4-meetings, computer training, and introduction to computer applications that are important in learning management at TK ABA. The results of data analysis showed that 83.33% of teachers had never received formal or non-formal IT training. The evaluation of community service activities shows that 100% of teachers are satisfied with the training provided. The aspect with the lowest level of satisfaction is related to the adequacy of the material provided in the training because it is still at the introductory level. Through the service activities carried out, it can be concluded that providing IT training for teachers of TK ABA is essential in supporting the management and learning at TK ABA Ponggalan, Giwangan. This, of course, can increase the trust of parents and the interest of prospective students in schools, which indirectly affects school income and welfare.